The Role of Cyber Law in Maintaining Digital Economic Security in Indonesia: a Study of E-Commerce and Online Transaction Security - Magfiroh, Diana; Fitrianti, Elvira; Sugiartini, Pegi (Politeknik Siber Cerdika Internasional, 2024)
Indonesia's digital economy is growing rapidly with e-commerce transactions continuing to increase. However, this is accompanied by increasing cyber threats that endanger the security of online transactions. Cyber law, through the ITE Law and the Personal Data Protection Law, plays a vital role in maintaining the security of these transactions, but its implementation still faces various challenges. This study aims to analyze the effectiveness of cyber law in protecting the security of e-commerce transactions in Indonesia, identify gaps in regulations, and provide recommendations for improving digital security. This study uses a qualitative method with a descriptive-analytical approach. Data were collected through in-depth interviews with experts and document analysis related to cyber law regulations and security incident reports. Samples were selected purposively from regulators, cybersecurity experts, and e-commerce representatives. The results of the study show that although cyber law regulations already exist, their implementation is not optimal. Many business actors have not complied with security standards, and law enforcement against violations is still weak. In addition, the National Cyber and Crypto Agency (BSSN) has an important role, but limited resources and coordination are obstacles. Public education about cyber security also still needs to be improved. Stronger collaboration between the government, private sector, and the community is needed to improve the security of online transactions, as well as stricter enforcement of regulations to create a safer e-commerce ecosystem in Indonesia. Cyber law, transaction security, e-commerce, data protection, regulation.